Mammalian fauna of Rajaji National Park, India: a review on ecological observations and checklist - Ritesh Joshi (Check List, 2016)
Rajaji National Park, in the Gangetic Plains biogeographic zone, has a diverse and biogeographically important mammalian assemblage. In the recent past, several studies on the herbivores, large carnivores and mega-herbivores have been carried out, but limited work has been done on the distribution of mammals in the park. This study illustrates the ecological observations and review of the mammals of the Rajaji National Park, based on field surveys, carried out during 2006–2008, using direct and indirect sampling methods. A total of 44 mammal species, belonging to nine orders and 20 families were recorded, which included one insectivore, six chiropterans, two primates, one pholidotan, 16 carnivores, one proboscidean, six artiodactylians, one lagomorph and 10 rodents. Of these, seven are classified as Endangered/Vulnerable in the IUCN Red List of Threatened Species; however, three species are Near Threatened, a lower risk category.